Pemanfaatan Limbah Sampah Organik di Pasar Ciputat Kota Tangerang Selatan - Tohiroh Tohiroh; Asep Surya Lesmana; Sukardi Sukardi; Hendra Candra; Joned C Saksana; Muhamad Arief Noor; Mohamad Fayruz; Adi Wicaksono; Retno Rizki; Rismayanti Rismayanti; Yet Heni Yanti; Dwi Pravitasari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
This activity aims to optimize the management and utilization of organic waste at Ciputat Market, South Tangerang City on June 2022, through the implementation of composting methods and the use of biodigester technology. The activities were conducted at Ciputat Market, a major economic hub with a significant volume of organic waste produced daily. The results show that the composting and biodigester methods significantly reduced the volume of organic waste. The compost produced is nutrient-rich and can be used as an effective natural fertilizer, while the biodigester technology converts organic waste into biogas, an environmentally friendly alternative energy source. This implementation not only helps to reduce waste issues at Ciputat Market but also provides economic benefits to the surrounding community by offering value-added products such as compost and biogas. This approach demonstrates great potential for more efficient and sustainable organic waste management in other traditional markets.